The Efficacy of Downward Counterfactual Thinking for Regulating Emotional Memories in Anxious Individuals - Parikh, Natasha; De Brigard, Felipe; LaBar, Kevin S. (Frontiers in Psychology, 2022)
Aversive autobiographical memories sometimes prompt maladaptive emotional responses and contribute to affective dysfunction in anxiety and depression. One way to regulate the impact of such memories is to create a downward counterfactual thought–a mental simulation of how the event could have been worse–to put what occurred in a more positive light. Despite its intuitive appeal, counterfactual thinking has not been systematically studied for its regulatory efficacy. In the current study, we compared the regulatory impact of downward counterfactual thinking, temporal distancing, and memory rehearsal in 54 adult participants representing a spectrum of trait anxiety. Participants recalled regretful experiences and rated them on valence, arousal, regret, and episodic detail. Two to six days later, they created a downward counterfactual of the remembered event, thought of how they might feel about it 10 years from now, or simply rehearsed it. A day later, participants re-rated the phenomenological characteristics of the events. Across all participants, downward counterfactual thinking, temporal distancing, and memory rehearsal were equally effective at reducing negative affect associated with a memory. However, in individuals with higher trait anxiety, downward counterfactual thinking was more effective than rehearsal for reducing regret, and it was as effective as distancing in reducing arousal. We discuss these results in light of the functional theory of counterfactual thinking and suggest that they motivate further investigation into downward counterfactual thinking as a means to intentionally regulate emotional memories in affective disorders.